The position of the yang Di Pertuan Agong under the constitutional monarchy / Zuraini Ariffin - Ariffin, Zuraini (Faculty of Law, 1987)
After the Second World War many new nations in Asia and Africa found it expedient to blow hot air and play up their newly won independence. Sometimes to the discomfort and sorrow of their well—wishers. But then the Alliance took over the government of Malaysia then emerged with Singapore and Borneo as new members of the family stable and progressive. And if Malaysia is to continue to enjoy the fruits of independence it is imperative that its people must continue to learn the lessons of history. So it can be a building force in welding the people together. We must often referred to what happened in the past, in the belief that the future will portend happiness for our people. Malaysia today comprises of thirteen states federated through her history in a gradual process of federation from the initial formation of the Straits Settlements in 1826, the Federated Malay States in 1896, and the Malayan Union in 1946 which subsequently became the Federation of Malaya in 1948.